Pengaruh Kompensasi dan Kompetensi terhadap Peningkatan Kinerja Pegawai (Survey pada Pegawai Universitas Widyatama) - Pawit Wartono; Ryan Kurniawan (Cakrawala Repositori IMWI, 2019)
The era of globalization demands progress in all areas including in education. The world of education is the only formal institution to answer all the challenges that occur. This is where the role of the institution of education providers becomes important, because in it there are components of Human Resources in demand to work with professional and good quality work that is expected to be able to improve the progres of the institution. The purpose of this study is to determine the picture of Compensation and Competence and Employee Performance at Widyatama University. In addition, this study also aims to determine how much Compensation and Competence will together afect employee performance at Widyatama University. This research was conducted on Employees at Widyatama University with 66 respondents. The data collection technique is done through questionnaire and direct observation and using descriptive analysis method verifikatif. As for testing the hypothesis used multiple regression analysis method to test the hypothesis used t test and F test at the level of α = 0.05 with the help of SPSS Version 20 and Microsoft Excel program. Based on the results of research shows the picture that the compensation of employees are in good category, employee competence is in good category, and Employee Performance is in good category. There is a positive influence and significant variable Compensation to Performance of 0.467 or 46,7%, while the Competence variable significantly influence Employee Performance of 0.321 or 32,1%. The effect of simultaneous Compensation and Competence on Performance of 0.576 or 57,6% and the rest of 0.424 or 42,4% is another variable that is not examined. The conclusion of this research is there is significant influence between Compensation and Competence to effort of improvement of Employee Performance at WidyatamaUniversity.